If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 100 = 6x + 4 Reorder the terms: 100 = 4 + 6x Solving 100 = 4 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 100 + -6x = 4 + 6x + -6x Combine like terms: 6x + -6x = 0 100 + -6x = 4 + 0 100 + -6x = 4 Add '-100' to each side of the equation. 100 + -100 + -6x = 4 + -100 Combine like terms: 100 + -100 = 0 0 + -6x = 4 + -100 -6x = 4 + -100 Combine like terms: 4 + -100 = -96 -6x = -96 Divide each side by '-6'. x = 16 Simplifying x = 16
| 3x+-3=-9 | | 7.3=8.5-0.6x | | 15=8x+3-6 | | -6y=1/4 | | (2x-4)*x=100 | | 3x/(x^2-x-20) | | 3x/x^2-x-20 | | 1nx=6 | | 2x-4*x=100 | | C=8pieg | | y=-3z-4 | | 1/(3y)=1/24 | | 3(7+w)=2(6+w) | | -25=4x-4 | | 7.4x-3.8=18.4 | | 6(x+4)+2=8x-2(x-5) | | 3x+4x-4=24 | | -2x+35=2x+15 | | Cos(x)-Cos^3(x)= | | 36x-9/2x^2 | | 3x(x+2)=7 | | 3x(x-2)=7 | | 8(x+1)+4=2x+6(2+x) | | 6x-48=2x+12 | | 3n=12-3n | | 100-4q=10+q | | 2x+78=68 | | 6(8n-1)+7=8(6n+8) | | 3y-0.5=1.4y+3.1 | | 72x-9/2x^2 | | M/4=-4.1 | | 3x-8y+45=0 |